The Effect of Leadership and Organizational Culture on Employee Performance With Job Engagement as A Mediation Variable - Netty Laura; Geby Sasmitha (Jurnal Ilmiah Sumber Daya Manusia, 2022)
The following research aims to analyze the influence of leadership, organizational culture, and job involvement on employee performance. This research was conducted on employees and female employees in the area of North Jakarta and its surroundings, where data collection used the distribution method. The following research population is employees who work in the North Jakarta area with 1-3 years of service. The number of respondents in the following research reached 150 people. The following research data processing technique uses the PLS (Partial Least Square) system. The results showed that organizational culture and work involvement had a significant effect on employee performance, but leadership had no significant effect on employee performance.